Selective enrichment of metal-binding proteins based on magnetic core/shell microspheres functionalized with metal cations1. Issue 12 (21st June 2015) - Fang, Caiyun; Zhang, Lei; Zhang, Xiaoqin; Lu, Haojie
<x xml:space="preserve">Abstract</x> A new method based on magnetic microspheres with metal ions was developed and applied to characterize putative metal binding proteins.